Tirana's Sub-Municipalities: Has All Been Considered - Sherko, Romeo (My University, 2002)
Extensive political and fiscal decentralization is now underway in almost all countries in Central and Eastern Europe and the former Soviet Union. Found under the apparent political pressures to decentralize and the potential economic advantages of doing so, Albanian government has been allocating significant efforts into the design and implementation of a reasonable decentralization law. This paper calls for the Albanian government to be cautious. Design of decentralization schemes that are inspired mainly by electoral and political processes without considering the fiscal and institutional dimensions cannot produce efficient results. Political decentralization is associated with the devolution of power to sub-national political entities. However, if decentralized entities in Albania are to execute the responsibilities passed to them, they will also require a suitable level of financial resources to cover the costs of providing local public goods and services. The issues are complex, technically, financially, and politically. How alternative policies impact local economic development is often difficult to assess and studies have some times shown contradictory results depending on the specific local contexts. Much more concrete analysis, based on sound local knowledge and data is needed to improve the design of the systems that are being put into place.
Keywords: Urban Land; Land Tenure Center; University of Wisconsin-Madison; Albania